14. PERAN ORGANISASI KERJA SAMA ISLAM (OKI) DALAM MENANGANI KONFLIK ETNIS RAKHINE-ROHINGYA DI MYANMAR TAHUN 2012-2013 - Rr. Tiara Ayu Dewinta; Reni Windiani; Marten Hanura (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
Human conflict between the Rakhine and Rohingya ethnics in Myanmar in 2012confiscated international society attention since it broke the human rights. This internalconflict incurred a lot of victims and increased the number of Rohingya refugees escapingto the neighbor countries indirectly engaging several countries, either IGO or NGO. One ofinternational organizations paying attention to this conflict was Organization of IslamicCooperation. This was an analytic descriptive research using library study method andapplying the liberalism and international organization theories. The objective of thisresearch was to find out the roles of Organization of Islamic Cooperation in ethnicalconflict of Rakhine and Rohingya in Myanmar in 2012. The result of this research showedthat the roles of Organization of Islamic Cooperation were including as the initiator,facilitator, and mediator. Organization of Islamic Cooperation had strived to run its rolesas the IGO in helping solve the conflict between Rakhine and Rohingya ethnics inMyanmar.